PENGARUAH KEMAMPUAN INTELEKTUALITAS DAN MORALITAS TERHADAP TINGKAT KESUKSESAN DALAM PENGEMBANGAN KARIER KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PADANG - Syahril Syahril (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Abstract : Based on data obtained from the PDAM (Padang Municipal Water Supply Company), that the ability of intellectual and morality determines the level of success in the career development of employees in the PDAM (Regional Drinking Water Company) of the City of Padang. Intellectual ability possessed by the employee will show the work procedures that are systematic and accurate, as well as the morale owned by this employee will determine the behavior of employees at work, because if employees have no intellectual ability and immoral, the level of success is difficult to achieve, while the PDAM (Regional Drinking Water Company) is a community owned so its employees must be demanded to have intellectual abilities and have good morals in accordance with the demands of the community, especially the people in the city of Padang.From the description of the background above, the main problem in this study is